2019
DOI: 10.1017/s0007485319000476
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent development and survival of immature stages of the coffee berry borer Hypothenemus hampei (Coleoptera: Curculionidae)

Abstract: Although the coffee berry borer, Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae) is the most destructive insect pest of coffee worldwide, there is much to learn about its thermal biology. This study aimed to develop temperature-based models for H. hampei development and to provide the thermal requirements of immature stages in the laboratory. Using a new observation method, larval development and survival were monitored daily on fresh Arabica coffee seeds, under seven constant temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 31 publications
4
25
0
4
Order By: Relevance
“…For the CBB, the lowest threshold temperatureis between 10 and 18 °C,as reported by many authors (Jaramillo et al, 2009, Ruiz-Cárdenas;Baker, 2010, Giraldo-Jaramillo;Garcia;. In the present study, all CBB stages completed their development at 16 °C.Some authors, such as Jaramillo et al (2009) and Azrag et al (2020) have reported that the CBB life cycle was not completed at 15 °C.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…For the CBB, the lowest threshold temperatureis between 10 and 18 °C,as reported by many authors (Jaramillo et al, 2009, Ruiz-Cárdenas;Baker, 2010, Giraldo-Jaramillo;Garcia;. In the present study, all CBB stages completed their development at 16 °C.Some authors, such as Jaramillo et al (2009) and Azrag et al (2020) have reported that the CBB life cycle was not completed at 15 °C.…”
Section: Resultssupporting
confidence: 80%
“…These values are lower than those obtained in other studies of the effect of temperature on the CBB life cycle over the range of 18 to 30 °C. In general, the higher the temperature, the shorter the life-cycle duration and the higher the survival and fertility (Jaramillo et al, 2009;Garcia;Parra,2018;Azrag et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, three studies have attempted to determine the effect of temperature on D. longicaudata albeit under various conditions of host species, host stage, and diet among others. Liu et al 2012 [45] conducted their investigations on third instar larvae of B. dorsalis but unfortunately in our experience, exposing larvae of this stage to gravid females of D. longicaudata results in encapsulation or [46] Although insects do not develop at a constant temperature in nature, temperature-dependent development models built from the experimental data provide biological information that can be used for understanding the distribution, seasonality, and population dynamics of the insect species [48,49]. For the natural enemies, knowledge of temperatures that favor or limit the development and population growth for the predator/parasitoid, as well as the areas where the natural enemy can establish are important in biological control programs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the influence that temperature exerts on the development and survival of insects 7,14,39 . Yet, because the response of insects to temperature is species‐specific, studies about the effect of temperature on insect biology are still relevant, particularly for agricultural and forest pests due to their application in pest management and prediction of species distributions under current and projected climate conditions using mechanistic or hybrid models 8,40–42 . In this context, knowledge of the thermal thresholds of insect pests may help in understanding the risks of a given species spreading to regions outside its native range.…”
Section: Discussionmentioning
confidence: 99%